Cooperative learning with SAVI approach to improve student learning outcomes class X SMK Gajah Mada Banyuwangi - Eko Prasetyo; Susiswo Susiswo; Erry Hidayanto (FMIPA UNIVERSITAS NEGERI MALANG, 2019)
The student learning outcomes are still low.we need to improve that. Cooperative learning with SAVI approach can be implemented to solve the problem above